Effect of Fabrication Methods on The Density and Impact Strength of Brake Pad Composites for Railway Application - Deni Fajar, Fitriyana; Muhammad Bustanul, Aripin; Saeful, Dimyati; Rusiyanto, Rusiyanto; Rahmat Doni, Widodo; Aldias, Bahatmaka; Samsudin, Anis; Wirawan, Sumbodo; Da Silva Guterres, Natalino Fonseca (INTI International University, 2023)
Railway brake pads, which are essential components of braking systems, are commonly manufactured using metallic or composite materials. Nevertheless, these technologies come with disadvantages such as a restricted lifespan and heightened intricacy during installation. The objective of this project was to create composite brake pad materials to minimize the utilization of metal brake pads and reduce the demand for imports. The study entailed fabricating brake pad samples with a composite material. The study produced railway brake pad samples by combining epoxy, hardener, rice husk, aluminium oxide, and iron oxide. The components were blended and subsequently put into a mold, where they were compacted to form compression molding products. The specimens were divided into sections to comply with the density and impact testing requirements set by American Society for Testing and Materials (ASTM). The obtained products were evaluated by a Charpy impact test and an electronic density meter. The study demonstrates that the manufacturing procedure has a substantial effect on the density of composite specimens. The hand layup result exhibits a density of 1.230 g/cm3 , the composite specimen produced using compression molding possesses a density of 1.696 g/cm3 . The compression molding technique results in a 38% increase in density compared to items made using the hand lay-up method. Applying high pressure and temperature during compression hot molding improves the bonding between fibers and the matrix, reduces the presence of empty spaces, and enhances the overall strength of the structure. The impact strength of compression molded items exhibits a 27% enhancement in comparison to hand lay-up products.